Fishers, let us talk: validating métiers in a multi-gear coastal fishing fleet - Szynaka, Monika (2022)
In the multi-gear coastal fleet in the Algarve (South Portugal), fishers own licenses for various fishing gears. However, they generally do not use all these licenses, and therefore, it is difficult to estimate the impacts this fleet has on the local environment. In this study, two types of questionnaires were used directed to the local fishers from the multi-gear fleet during interviews carried out between November 2019 and July 2021 with the objective to validate the métiers proposed for this fleet in a previous study using multivariate analysis on past landing profiles. A total of 10 out of the 11 proposed métiers were validated, including four métiers with gillnets, three with dredges, two with trammel nets, and one with traps. Additional métiers were identified not found in the previous study. The results obtained with the two types of questionnaires are presented, and their usefulness in validating the gear used and the seasonality of fishing activities are discussed, as well as their contribution to a clearer distinction between target species and commercial by-catch.